Competitiveness Analysis of Indonesian Banking Industry Based on Corporate Social Responsibility Impacts - ., Lindiawati (International Journal Of Management And Economics Invention, 2021)
Corporate Social Responsibility (CSR) has been becoming more attention for both companies and consumers. People are more aware of giving consideration on what companies have been doing for public as the representative of their responsibilities, and they use this to make buying decision and producing word-of-mouth. Corporate Social Responsibility has also been involved in banking industry since bank is an industry that is considered fragile or very easy to be affected by publis psychology leading bank customers then rush during a negative issue impacting the bank industry. By the government regulation pushing the banks to implement CSR, the kinds of CSR activities must reflect what banks wanth to achieve. Based on some studies on CSR impacts, it has been identified that the impact of CSR activities can be classified into four categories namely: phylanthophy, promotion, business impact, and mindset change. By knowing the map of the banks’ CSR activities based on those four categories, it can be concluded the competitiveness of the bank especially from the perspective of their social exposures. The result shows There are four banks that have well implemented CSR in term of that they have many CSR activities and whose impact level s are high. Three of of the four banks, have completed CSR whose impacst are complete, namely philanthropy, promotion, Business Impact, and Mindset Change.